Comparison of the different monosodium urate crystals in the preparation process and pro-inflammation - Fei Yan; Hui Zhang; Xuan Yuan; Xuefeng Wang; Maichao Li; Youlin Fan; Yuwei He; Zhaotong Jia; Lin Han; Zhen Liu (Advances in Rheumatology, 2023)
Abstract Objectives The deposition of monosodium urate (MSU) crystals within synovial joints and tissues is the initiating factor for gout arthritis. Thus, MSU crystals are a vital tool for studying gout’s molecular mechanism in animal and cellular models. This study mainly compared the excellence and worseness of MSU crystals prepared by different processes and the degree of inflammation induced by MSU crystals. Methods MSU crystals were prepared using neutralization, alkali titration, and acid titration methods. The crystals’ shape, length, quality, and uniformity were observed by polarized light microscopy and calculated by the software Image J. The foot pad and air pouch models were used to assess the different degrees of inflammation induced by the MSU crystals prepared by the three different methods at different time points. Paw swelling was evaluated by caliper. In air pouch lavage fluid, inflammatory cell recruitment was measured by hemocytometer, and the level of IL-1β, TNF-α, and IL-18 by ELISA. Inflammatory cell infiltration was assayed by immunohistochemistry of air pouch synovial slices. Results For the preparation of MSU crystals with the same uric acid, the quantity acquired by the alkalization method was highest, followed by neutralization, with the acid titration method being the lowest. The crystals prepared by neutralization were the longest. The swelling index of the foot pad induced by MSU crystals prepared by acid titration was significantly lower than that of the other methods at 24 h. The inflammatory cell recruitment and level of IL-1β, TNF-α, and IL-18 in air pouch lavage fluid were lowest in animals with crystals prepared by acid titration. IL-1β secretion induced by MSU crystals prepared by acid titration was significantly lower than that of the other two groups, but there was no significant difference in IL-18 secretion between the three groups in THP-1 macrophages and BMDMs. Conclusions All three methods can successfully prepare MSU crystals, but the levels of inflammation induced by the crystals prepared by the three methods were not identical. The degree of inflammation induced by MSU crystals prepared by neutralization and alkalization is greater than by acid titration, but the quantity of MSU crystals obtained by the alkalization method is higher and less time-consuming. Apparently, the window of inflammation triggered by acid titration preparation is shorter compared to other forms of crystal preparation. Overall, MSU crystals prepared by the alkaline method should be recommended for studying the molecular mechanisms of gout in animal and cellular models.